The Effectiveness of Guided-Discovery and Instructional Media on Early Mathematical Skills - Mariyana, Rita (Indonesian Journal of Early Childhood Education Studies, 2019)
Early mathematics skills are basic skills that children need to have to adapt to the external challenges of the 21st century. To empower early mathematical abilities, the guided discovery method works effectively. The objective of this study is to find out the effectiveness of guided discovery and instructional media toward early mathematics skills kindergarten student. This research was a quasi-experimental. The instrument for obtaining data on children?s early mathematical abilities is the observation sheet of early math abilities. The sampling technique employed was the multi stage random sampling method. The study was conducted on kindergarten children in West Java Province, Indonesia. The results showed that there were significant differences from guided discovery and instructional media to children?s mathematical abilities.